Sex-related differences in genetically determined Alzheimer’s disease - Del Hoyo Soriano, Laura; Wagemann, Olivia; Bejanin, Alexandre; Levin, Johannes; Fortea, Juan (Frontiers in Aging Neuroscience, 2025)
We reviewed the literature on sex differences in genetically determined Alzheimer’s disease (AD), focusing on autosomal dominant AD (ADAD), Down syndrome-associated AD (DSAD), and APOE4 homozygosity, particularly regarding disease penetrance, symptom onset and clinical progression, and trajectories for markers of amyloidosis (A), tau pathology (T) and neurodegeneration (N). Data suggests that sex differences in disease penetrance, symptom onset, and AT(N) biomarker trajectories are typically subtle for genetically determined AD populations. Noteworthy exceptions, such as increased neurodegeneration in later stages of the disease in females while similar cognitive outcomes, suggest a potential differential cognitive reserve that warrants further investigation. Additionally, the interaction between APOE genotype and sex reveals complex and multifaceted effects in DSAD, with potential implications for ADAD that remain underexplored. The smaller sex differences observed compared to sporadic AD offer insights into the different underlying disease mechanisms in genetically determined AD populations. Future research should prioritize sex-specific investigations in genetically determined AD, focusing on refining methodologies. This includes prioritizing longitudinal designs, adjustment for key confounders, and adherence to sex-specific guidelines.